2011
DOI: 10.1111/j.1750-3841.2011.02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Effect of Natural Antioxidant Compounds on Hazelnut Oil Oxidation by Adaptive Neuro‐Fuzzy Inference System and Artificial Neural Network

Abstract: In this study, natural compounds including gallic acid, ellagic acid, quercetin, β-carotene, and retinol were used as antioxidant agents in order to prevent and decrease oxidation in hazelnut oil. Quercetin showed the strongest antioxidative effect among the antioxidative agents, during storage. The accuracy of adaptive neuro-fuzzy inference system (ANFIS) and artificial neural network (ANN) models was studied to estimate the oil samples' peroxide value (PV), free fatty acid (FFA), and iodine values (IV). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 40 publications
(46 reference statements)
3
11
0
Order By: Relevance
“…The results indicated that the ANFIS model with a high coefficient of determination ( R 2 = 0.999) had better performance compared to ANN ( R 2 = 0.89). Moreover, the ANFIS used was a more effective modelling technique for the estimation of PV of hazelnut oil in the presence of natural antioxidant compounds during storage in comparison with ANN . In another study, the rheological characteristics of different molasses types were satisfactorily predicted in the ANFIS model with high coefficient of determination ( R 2 = 0.979–0.999) and low root mean square error (RSME) (0.12–0.46), depending on the model structure such as membership function type and number .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the ANFIS model with a high coefficient of determination ( R 2 = 0.999) had better performance compared to ANN ( R 2 = 0.89). Moreover, the ANFIS used was a more effective modelling technique for the estimation of PV of hazelnut oil in the presence of natural antioxidant compounds during storage in comparison with ANN . In another study, the rheological characteristics of different molasses types were satisfactorily predicted in the ANFIS model with high coefficient of determination ( R 2 = 0.979–0.999) and low root mean square error (RSME) (0.12–0.46), depending on the model structure such as membership function type and number .…”
Section: Introductionmentioning
confidence: 99%
“…Processing the information occurs in each neuron at the same time as other units do. Indeed, the network is trained with a dataset of observations (inputs and outputs) and optimised based on its efficiency to predict a set of known outcomes . As is known, food structures are non‐linear systems which ANNs can successfully model their parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Humans live in a highly oxidative environment, and many processes involved in metabolism may result in the production of excess free radicals, which can lead to health problems . Oxidation causes the formation of toxic compounds that are harmful to human health, such as reactive oxygen species and free radicals, which can lead to carcinogenesis, mutagenesis, inflammation, DNA changes, aging, cardiovascular disease and nutritional loss . In addition, oxidation may result in unpleasant flavor and rancid taste .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CFWNN's prediction results are compared with those obtained by MLP networks and adaptive neuro-fuzzy inference system (ANFIS) identification models. Such schemes have become popular modeling techniques in food science and technology in recent years [14]. In the proposed CFWNN, 10 final rules have been created, using the clustering pre-processing stage.…”
Section: Resultsmentioning
confidence: 99%